Sosialisasi Dan Implementasi Eco paving Block Untuk Pemberdayaan Masyarakat Industri Kecil - Nursiah Chairunnisa; Ratni Nurwidayati; Husnul Khatimi (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2022)
In South Kalimantan, coconut shell waste is enormous and is not utilized massively by the local community so that it covers river mouths and even fills the bottom of warehouses and people's houses, and waste/used coconut shells have piled up. This condition causes the river mouth to narrow so that it becomes a problem that is quite disturbing to the local community. Currently, most of the shell waste is used and only used as handicrafts and making briquettes. The use of coconut shell waste for paving blocks is one solution to utilize coconut shell waste into construction materials that support eco-green construction by reducing the cement content. Empowerment of local communities to process coconut shell waste as an eco-paving block construction material is useful in the long term for local communities and supports government programs in implementing the eco-green construction concept. Therefore, the initial step taken was socialization and implementation for small industry partners providing paving blocks in Banjarbaru, South Kalimantan related to manufacturing coconut shell waste as a building material for eco paving blocks. Furthermore, the results of this eco paving block are expected to be further disseminated to local communities to independently make eco paving blocks that can later be used for the construction of public space facilities and green open spaces